(untitled) (Research, Society and Development, 2022)
In this article we propose to present the pedagogical practices developed by teachers in classes mediated by technology, of professional education, referring to the teaching process of students with special educational needs. The pandemic and the inevitable closure of schools have increased gaps in the education sector around the world and in Brazil, which was already big, it has gotten even bigger. Thus, teaching and learning in isolation has become a challenge. Since an inclusive school has the student as the protagonist of all educational action, where the curriculum and interventions must adapt to them and not the other way around, we seek answers to this challenge during this context, as the teachers of professional education carried out the process education? The pandemic and its countless questions that reveal themselves in the face of this dark time and at the same time of discoveries and reinventions. Far from the blackboards and now behind the screens, teachers have been working hard to overcome this never-before-imagined challenge, and which until then had not been trained to do so.